Assessment of Smallholder Farmers’ Perception on Extension Training Programs for Entrepreneurial Skills Development in Cross Rivers State. - Victor, Okpodu; Olufemi, Oladunni; Ehirim, Nnamdi Chukwuemeka; Samson, Awoyemi (Archives of Business Research, 2020)
The study of smallholder farmers’ perception on extension training delivery for entrepreneurship skills in cross rivers state was done to assess their perceived factors of entrepreneurial development in the study area and to examine the relationship between extension training delivery on entrepreneurship skills and the effectiveness in linking farmers to the market. Data were collected using a two stage random sampling of 114 small holder farmers registered with Agricultural Development Programme of the state and later analyzed using descriptive statistics; Pearson Product Moment Correlation Coefficient; and Factorial Analysis. Result reveal that the farmers are mostly male (63.2%) with a mean age of 46year. The Pearson Product Moment (PPM) Correlation Coefficient showed no significant relationship between some selected socioeconomic characteristics of the respondents and the perceived effectiveness of extension service delivery on entrepreneurship training. Meanwhile, marital status, years of formal education and farming experience were all significant at 95% level in terms of effective contribution of extension services to farmers’ entrepreneurial skills. Again, it was shown in the factor analysis that three significant variable as contributing significantly to the predictive ability of the model. These are training improving marketing skill (0.037), communication skill of the agent in training (0.025) and farm and home visit of extension agent (0.018). Based on the findings, the study recommended that extension services is an important source of socioeconomic change in promoting entrepreneurship skills need of the farmers in the study area.